Measuring and Analysis of Demand Function on Oil derivatives of A Selected countries the Period 1985- 2008 - عبد الحسين, هناء; عطية, قحطان لفته (Journal of Economics and Administrative Sciences, 2011)
The subject of demand on oil derivative has occupied an important position at present time in the daily life context. The fuel of benzene and gas oil and kerosene is one of basic elements of that concern, and on local , regional and international levels. The oil derivatives have played a leading role in determining the course and nature of development since early 1970 to the present time whether in the productive Arab countries or the importing. The researcher set out from the hypothesis that the increase of the local consumer demand on some of the oil derivatives is because of the internal and external factors accompanied by the inability of the productive capability and local production to confront this increase, and the resort to the importing of these derivatives to satisfy the need of local market. The research aims at determining the level of local consumer demand on the basic oil derivatives and the level of demand on the imported oil derivatives to satisfy the need of local market after Knowing the nature of external and internal factors affecting the level of demand. Also, a future anticipation of the demand on the basic oil derivatives for the sample countries for the period 2009- 2018, and it was found that the oil products are more tending towards the basic products benzene, fluid gas oil and kerosene, which have witnessed an annual increasing of rate %2.1 during the last ten years with an inability of the local product to keep up with that consumption. The result is an expanding gap between the two. The interest of the Arab countries as petroleum producers lurks in oil processing and transforming it into oil derivatives. There is no pretext, political or economical, that deny that legal anticipation of Arabcountries. It is also impermissible economically to export oil as raw material without processing it.